Perlindungan Hukum Terhadap Anak Korban Toxic Parenting Dalam Perspektif Hukum Islam - Lubis, Yulia Khairani; Siregar, Fatahuddin Aziz; Gunawan, Hendra (Jurnal El-Thawalib, 2024)
The problem in this research is legal protection on children suffering toxic parenting in the Labuhanbatu district in the perspective of Islamic law. The type of research in this study is field research, using qualitative approaches, the primary data source of children to experience toxic parenting in the family in 2021-2022 and the caretaker of the women and child protection services (DPPPA), A secondary source of data consists of books, journals, and documents related to the study. The data-gathering techniques used are interviews, observations, and documentation. The data-analysis techniques use qualitative descriptive. That the protection of law in labuhanbatu district is good enough because there is an institution that serves to protect children: the women's protection and child protection service (DPPPA), by performing socialization, and protecting children by providing mediation services, legal aid, and psychological recovery, according to the 2014 35th act on child protection, while it is the perspective of Islamic law that children should be protected from all that could lead to the exclusion of children's rights, Like the one in QS. At-Tahrim: 66, which is the right to an education, a living, protection, and nurturing, and hampering growth of children, for in the perspective of Islamic law the violent behaviour of children is strictly prohibited except in education and worship, it should fit within some provisions, it is according to Ahmad bin Hanbal that the Prophet SAW forbids such violence as beating and educating children, And also, in the opinion of clerics educating children with violence, is not recommended according to dalil-dalil, both the Qur'an and As-Sunnah. Therefore, legal protection in the Labuhanbatu district is in keeping with an Islamic law perspective that prohibits violent child abuse.